Integration of multisources data for quarry slope stability assessment in the Itaoca district (Southeastern Brazil) - Hartwig, Marcos Eduardo; Moreira, Cesar Augusto [UNESP] (Acad Brasileira De Ciencias, 2021)
Usually, stability conditions of excavation slopes are evaluated by means of kinematic analysis and geomechanical classification systems. However, field surveys are concentrated at the slope toe and information about the upper and internal portions of rock masses are not taken into account. In order to tackle with these issues multisources data were integrated. The studies were carried out in a marble quarry located in one of the largest Brazilian poles of dimension stones. Results have shown that drone images actually help in the structural characterization of rock masses because they allow to classify variable degrees of fracturing and to identify structural domains in the entire slope face. In addition, the number of discontinuities interpreted from drone images was much larger than that determined by scanline survey methods. This demonstrates that the subsampling of classical survey methods may significantly affect slope stability assessment. Results have also shown that the intensive use of explosives as a method for rock dismantling was an important mechanism of fracture generation. The electrical resistivity tomography method coupled with the other survey methods employed in this work, proved an important tool for rock mass characterization and quarry exploitation, since it allowed identifying and assessing subsurface fractured zone.
Keywords: drone remote sensing; electrical resistivity tomography; kinematic analysis; Rock Mass Rating; structural survey